2016
DOI: 10.1037/cap0000066
|View full text |Cite
|
Sign up to set email alerts
|

Challenges facing East Asian immigrant children in sexual abuse cases.

Abstract: Immigrants from East Asia make up 14.21% of the total number of immigrants in Canada. These families face many challenges as they acculturate to North America, but, sadly, some of these children may be at risk for sexual abuse. In this article, we outline the ways in which East Asian children, compared with Western nonimmigrant children, are at a particular disadvantage when considering prosecution of those who perpetrate abuse. We focus specifically on 3 areas of concern: (1) cultural differences that can sha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 60 publications
0
2
0
Order By: Relevance
“…For instance, in child sexual abuse cases, the perpetrator was often closely related to the child victim (e.g., relatives and family friends) (Connolly, Chong, Coburn, & Lutgens, 2015). Eastern immigrant children may be hesitant to recall these negative events given that doing so would inevitably threaten family harmony (e.g., reporting a family friend/relative who involved in the alleged crime) (Roberts, Qi, & Zhang, 2016). Examining cultural differences in remembering negative social‐focused events could reveal possible barriers that may disadvantage ethnic minority children in the legal system.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, in child sexual abuse cases, the perpetrator was often closely related to the child victim (e.g., relatives and family friends) (Connolly, Chong, Coburn, & Lutgens, 2015). Eastern immigrant children may be hesitant to recall these negative events given that doing so would inevitably threaten family harmony (e.g., reporting a family friend/relative who involved in the alleged crime) (Roberts, Qi, & Zhang, 2016). Examining cultural differences in remembering negative social‐focused events could reveal possible barriers that may disadvantage ethnic minority children in the legal system.…”
Section: Discussionmentioning
confidence: 99%
“…Understanding immigrants' cultural contexts is central for their recovery from sexual abuse. For example, a study in Canada revealed that East Asian young immigrants' cultural and linguistic context shaped their recall of traumatic memories, and thus, it affected the way these young immigrants disclosed sexual abuse (Roberts et al 2016). The researchers concluded that culture specific ways of recalling traumatic memories minimized the opportunities to prosecute the perpetrators.…”
Section: Culturally Relevant Trauma-informed Psychotherapymentioning
confidence: 99%